2015
DOI: 10.1073/pnas.1503477112
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule analysis of RAG-mediated V(D)J DNA cleavage

Abstract: The recombination-activating gene products, RAG1 and RAG2, initiate V(D)J recombination during lymphocyte development by cleaving DNA adjacent to conserved recombination signal sequences (RSSs). The reaction involves DNA binding, synapsis, and cleavage at two RSSs located on the same DNA molecule and results in the assembly of antigen receptor genes. We have developed singlemolecule assays to examine RSS binding by RAG1/2 and their cofactor high-mobility group-box protein 1 (HMGB1) as they proceed through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…To determine HMGB1's role as a cofactor, we conducted experiments with both 50 nM RAG1/2 and 50 nM HMGB1 in solution. Previous studies have hypothesized roles for HMGB1 in stabilizing the RAG1/2 nucleoprotein complex and increasing RAG1/2 binding affinity for RSS substrates (21,22). We found that FRET distribution for the 12RSS substrate was narrowed in the presence of RAG-HMGB1 complex in comparison with RAG1/2-only conditions (Fig.…”
Section: Rag Complex Induces Conformational Changes In 12rss and 23rsssupporting
confidence: 49%
See 2 more Smart Citations
“…To determine HMGB1's role as a cofactor, we conducted experiments with both 50 nM RAG1/2 and 50 nM HMGB1 in solution. Previous studies have hypothesized roles for HMGB1 in stabilizing the RAG1/2 nucleoprotein complex and increasing RAG1/2 binding affinity for RSS substrates (21,22). We found that FRET distribution for the 12RSS substrate was narrowed in the presence of RAG-HMGB1 complex in comparison with RAG1/2-only conditions (Fig.…”
Section: Rag Complex Induces Conformational Changes In 12rss and 23rsssupporting
confidence: 49%
“…The effect of RAG1/2 complex binding to RSS DNA was previously addressed using biochemical and biophysical techniques (19,20,22,26) and more recently visualized within the PC in structural analysis (see SI Discussion) (14). These studies indicated that binding of HMGB1 and RAG1/2 induced bending in both the 12RSS and 23RSS DNA substrates as well as in each substrate within the PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic RSSs. We chose a 12RSS flanking the immunoglobulin κ variable (IgκV) gene segment, V4-57-1, as the reference sequence due to its use in a previous TPM study on RAG-RSS interactions (20) for our reference sequence. This sequence has also been used in structural studies of RAG-RSS complexes (13,15), allowing us to compare our results with known information on the RAG-RSS structure.…”
Section: Resultsmentioning
confidence: 99%
“…2C). TPM has been applied to track the dynamic behavior of various protein-DNA systems, including RAG and RSS (16)(17)(18)(19)(20)(21). It is with the temporal resolution provided by TPM that we can track the full progression of individual RAG-RSS interactions from PC formation to cleavage.…”
mentioning
confidence: 99%